2013
DOI: 10.4161/psb.24686
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of signaling crosstalk between brassinosteroids and gibberellins

Abstract: Brassinosteroids (BRs) and Gibberellins (GAs) are two principal groups of growth-promoting phytohormones. Accumulating evidence supports that there are crosstalks between BR and GA signaling pathways. However, a molecular mechanism for direct signaling crosstalk between BRs and GAs was not revealed until recently. Works from three different groups demonstrated that an interaction between BZR1/BES1 and DELLAs, two groups of key transcriptional regulators from the BR and GA signaling pathways, respectively, medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 82 publications
0
28
0
Order By: Relevance
“…Reductions in BES1 and BZR1 led to a semidwarf phenotype, and dominant mutations in BES1 and BZR1 resulted in distinct phenotypes in plants grown under light [10,21,25]. Finally, another study revealed that BZR1 synergized with gibberellin to regulate cell elongation [14,[26][27][28].…”
Section: Discussionmentioning
confidence: 96%
“…Reductions in BES1 and BZR1 led to a semidwarf phenotype, and dominant mutations in BES1 and BZR1 resulted in distinct phenotypes in plants grown under light [10,21,25]. Finally, another study revealed that BZR1 synergized with gibberellin to regulate cell elongation [14,[26][27][28].…”
Section: Discussionmentioning
confidence: 96%
“…As it can be seen from the Figure 3, hybrid ZP 434 had statistically significant differences at concentration of 5.2×10 -7 , 5.2×10 -9 and 5.2×10 -15 M, while hybrid ZP 704 had higher sensitivity for 24-EBL range, with more statistically significant differences, relative to 24-EBL concentrations. Seed germination and seedling elongation (and in the later stages of plant development) are directly dependent on gibberellins inducing activity of the enzyme α-amylase, one of the key enzymes in the process of degradation of the starch reserves during seed germination with which BRs act synergistically [16,17].…”
Section: Resultsmentioning
confidence: 99%
“…We consider direct crosstalk between the BR and GA signalling pathways. Besides shared gene expression, two main mechanisms for BR-GA crosstalk have been suggested: direct interaction at the level of transcription factors BZR and DELLA [31], and BZR-mediated biosynthesis of GA [56]. Here we derive a mathematical model to compare the behaviour of the system under the three different mechanisms of crosstalk (interaction between BZR and DELLA, BZR-mediated biosynthesis of GA, and a combination of both of them) and to analyse their effects on the BR and GA signalling processes.…”
Section: The Crosstalk Modelmentioning
confidence: 99%